2020
DOI: 10.25259/ijms_140_2020
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate of cervical cancer from a study conducted in India

Abstract: Objectives: The incidence and mortality rates of cervical cancer in the world are 13.1/105 and 6.9/105, respectively. In India, it is estimated that there are 96,922 new cervical cancer cases and 60,078 deaths and ranked second among women cancers. The incidence and mortality rates are 14.7/105 and 9.2/105, respectively, although the incidence varies within Indian population. The majority of these cervical patients report at a late-stage of disease in health-care facility due to lack of awareness. A premier te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 20 publications
2
25
1
Order By: Relevance
“…The age-standardized incidence and death rates of cervical cancer is found to be 13.10 and 7.38 per 100,000 females. Consistent with our ndings, researchers found the age-standardized incidence and mortality rates of cervical cancer to be 14.7 and 9.2 per 100,000 among Indian women (Balasubramaniam et al, 2020). Similarly, researchers at George institute also found the age-standardized incidence and mortality rates of cervical cancer to be 22 and 12.4 per 100,000 women.…”
Section: Discussionsupporting
confidence: 88%
“…The age-standardized incidence and death rates of cervical cancer is found to be 13.10 and 7.38 per 100,000 females. Consistent with our ndings, researchers found the age-standardized incidence and mortality rates of cervical cancer to be 14.7 and 9.2 per 100,000 among Indian women (Balasubramaniam et al, 2020). Similarly, researchers at George institute also found the age-standardized incidence and mortality rates of cervical cancer to be 22 and 12.4 per 100,000 women.…”
Section: Discussionsupporting
confidence: 88%
“…The outcomes of women with cervical cancer in developing countries are lower compared with those in developed nations for various reasons [17]. First, the availability of treatment units is not uniform, with most of the needy not having access to treatment due to geographical reach, with most units in urban areas [18]. Second, completion of treatment is a challenge due to protracted treatment times and financial constraints.…”
Section: Treatment and Outcomesmentioning
confidence: 99%
“…Again, no separate subgroup analysis was done in their trial. A recent trial by Balasubramaniam et al (23) reported 5-year survival rates of 85% for stage 2 and 71.1% for stage 3 patients treated with standard radiation and chemotherapy arm. Grade 2 and above toxicities were slightly higher in arm B but the results were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%